Primary Hyperparathyroidism due to Parathyroid adenoma presenting as recurrent acute pancreatitis - Tarun J George (Asian Journal of Medical Sciences, 2017)
Primary hyperparathyroidism (PHPT) due to parathyroid adenoma presenting as recurrent acute pancreatitis is a rare entity. A 17-year-old male presented with recurrent attacks of pancreatitis and was found to have elevated serum calcium and Parathyroid hormone levels, 11.9mg/dL (8.5-10.2 mg/dL) and 396 pg/ml (10-65pg/ml) respectively. USG neck showed a 1.1 x 0.9 cm hypoechoic nodule in the superior aspect of left thyroid lobe. Parathyroid scintigraphy findings were consistent with parathyroid adenoma. After recovery of pancreatitis, surgical excision of the adenoma was done and the histopathological findings confirmed parathyroid adenoma. There were no further recurrence of pancreatitis following the excision.